Using focus groups in medical education research: AMEE Guide No. 91 - Stalmeijer, Renée E.; McNaughton, Nancy; Van Mook, Walther N. K. A. (Medical teacher, 2014)
Abstract Qualitative research methodology has become an established part of the medical education research field. A very popular data-collection technique used in qualitative research is the "focus group". Focus groups in this Guide are defined as "... group discussions organized to explore a specific set of issues ... The group is focused in the sense that it involves some kind of collective activity ... crucially, focus groups are distinguished from the broader category of group interview by the explicit use of the group interaction as research data" (Kitzinger 1994, p. 103). This Guide has been designed to provide people who are interested in using focus groups with the information and tools to organize, conduct, analyze and publish sound focus group research within a broader understanding of the background and theoretical grounding of the focus group method. The Guide is organized as follows: Firstly, to describe the evolution of the focus group in the social sciences research domain. Secondly, to describe the paradigmatic fit of focus groups within qualitative research approaches in the field of medical education. After defining, the nature of focus groups and when, and when not, to use them, the Guide takes on a more practical approach, taking the reader through the various steps that need to be taken in conducting effective focus group research. Finally, the Guide finishes with practical hints towards writing up a focus group study for publication.